Are the Bailouts Immune to EU Social Challenge Because They Are Not EU Law?. (26th January 2015) - Kilpatrick, Claire
Abstract : European Union's 'social constitution' and bailout measures – Are the bailout measures EU law? – Do the bailout measures create legal obligations? – Legal nature of Memoranda of Understanding – Avenues for challenge – Call for recognition of the EU law nature of bailouts and the costs of such non-recognition